Don’t Mind the Hypocrisy: a Commentary on Differentiated Treatment in Refugee Reception - Mickelsson Blomqvist, Tony (Socialinė teorija, empirija, politika ir praktika, 2023)
The current conflict in Ukraine has forcibly displaced a large number of people and has put migration issues at the center of attention once again. A small, but growing, body of literature has revealed that Ukrainian refugees are being treated differently vis-à-vis other refugee groups – this is a clear concern for the social work profession, which is supposed to safeguard all minorities’ rights equally. In this commentary, I briefly review and focus on one aspect of why Ukrainian refugees are seemingly being treated ‘better’ – culture. Cultural proximity has been argued to be a major factor in how the Western response to the current conflict has been shaped, where Ukrainians, but not other refugee groups, are conceived of as culturally compatible with Western countries. The commentary conceptualizes this treatment within the framework of ‘promising victimhood’ and suggests that further research should focus on how victimhood is constructed within the social work profession in relation to the current crisis.